WOMEN EMPOWERMENT THROUGH ENTREPRENEURSHIP: A CASE STUDY OF A SUCCESSFUL WOMEN DAIRY ENTREPRENEUR - Dr. Rumia Begum (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
India is the largest milk producing country in the world with 176.3 mt of milk in 2017-18 (Basic Animal Husbandry Statistics, DAHD&F, Govt. of India). Milk is one of the important components of the dairy farming which is helpful in enhancing the income of the rural households. Dairy farming is mainly dominated by the women (Arti et al 2019). Women entrepreneurship through dairy farming is an important source of income and employment for women as well as for others.